2018
DOI: 10.1016/j.compfluid.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A monolithic ALE Newton–Krylov solver with Multigrid-Richardson–Schwarz preconditioning for incompressible Fluid-Structure Interaction

Abstract: In this paper we study a monolithic Newton-Krylov solver with exact Jacobian for the solution of incompressible FSI problems. A main focus of this work is on the use of geometric multigrid preconditioners with modified Richardson smoothers preconditioned by an additive Schwarz algorithm. The definition of the subdomains in the Schwarz smoother is driven by the natural splitting between fluid and solid. The monolithic approach guarantees the automatic satisfaction of the stress balance and the kinematic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 57 publications
3
55
0
Order By: Relevance
“…In the following, we focus on the analysis of the momentum balance, and we briefly describe the role of the function k()monospacexfalse^ in Equation (11). For a full description of the PDE system (10)‐(14), please refer to Aulisa et al Equation (12) describes, in a monolithic form, the solid and fluid momenta, which are also referred to as the incompressible nonlinear elasticity equation and the Navier‐Stokes equation, respectively. The symbols ρ f and ρ s denote the mass densities for the fluid and solid part, respectively, whereas f f and f s indicate the body force densities.…”
Section: Numerical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following, we focus on the analysis of the momentum balance, and we briefly describe the role of the function k()monospacexfalse^ in Equation (11). For a full description of the PDE system (10)‐(14), please refer to Aulisa et al Equation (12) describes, in a monolithic form, the solid and fluid momenta, which are also referred to as the incompressible nonlinear elasticity equation and the Navier‐Stokes equation, respectively. The symbols ρ f and ρ s denote the mass densities for the fluid and solid part, respectively, whereas f f and f s indicate the body force densities.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Recent works showed that the above equation ordering is ill‐conditioned for steady‐state problems, and it becomes unstable for time‐dependent problems as the time step increases. Such a behavior can be easily explained by looking at the diagonal terms Kmonospaceds and Smonospaceus in the first and third rows of (26).…”
Section: Preconditionersmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid motion is described in a Lagrangian way, while the fluid is observed in Eulerian fashion. The deformation of the fluid domain is taken into account according to an arbitrary Lagrangian‐Eulerian (ALE) approach, which is one of the most popular techniques in the FSI community . To solve the FSI system, we use a monolithic Newton‐Krylov solver preconditioned by a geometric multigrid algorithm .…”
Section: Modeling Of the Mdt‐fsi Problemmentioning
confidence: 99%
“…We describe the solid motion in a Lagrangian way, while the fluid is observed in Eulerian fashion. The deformation of the fluid domain is taken into account according to an Arbitrary Lagrangian Eulerian (ALE) approach, which is one of the most popular techniques in the FSI community ( [4], [13], [23], [29]). To linearize the FSI system, Newton linearization is performed, therefore the evaluation of the Jacobian associated to the fluid-solid coupled state equations is required.…”
Section: Introductionmentioning
confidence: 99%